Invasive Mucinous Adenocarcinoma Associated with Adjacent Sessile Serrated Lesion of the Appendix Vermiform: A Case Report. (9th July 2014) - Kinoshita, Osamu; Murayama, Yasutoshi; Kuriu, Yoshiaki; Nakanishi, Masayoshi; Sakakura, Chohei; Otsuji, Eigo
Abstract : Although the definition of sessile serrated lesion (SSL) of colon is controversial and the risk of progression to malignancy is also under investigation at present, SSL is generally described as a polyp characterized by a serrated architecture. It is estimated to represent a feature of a new cancerization pathway, coined "serrated neoplasia pathway, " particularly in right-sided colon adenocarcinomas. On the other hand, in appendix, the role of this pathway remains uncertain, probably because very few cases of appendiceal adenocarcinoma associated with SSL were reported, and furthermore, immunohistochemical examination was rarely carried out. We herein report an interesting case of invasive appendiceal mucinous adenocarcinoma exhibiting SSL, which was pathologically estimated as a potential precursor lesion, and performed representative immunohistochemistry for both the mucinous adenocarcinoma and SSL in the same specimen. To further elucidate the progression of the appendiceal carcinoma from SSL, both an adequate sectioning of the lesion and systematic immunohistochemical examination of a large number of appendiceal carcinoma cases containing adjacent SSL would be required.